Perfluorohexyloctane: More than Meets the Eye? - Alijagic, Andi; Oresic, Matej; Hyötyläinen, Tuulia (American Chemical Society (ACS), 2026)
Perfluorohexyloctane (F6H8) is a semifluorinated alkane increasingly used in medical applications. Emerging evidence, however, indicates that this compound can persist in biological systems and influence cellular processes. These observations suggest that the exceptional stability of F6H8, while beneficial for medical performance, may also have implications for long-term biological and health outcomes.